IMPROVING STUDENT’S SCIENCE NUMERATION CAPABILITY THROUGH THE IMPLEMENTATION OF PBL MODEL BASED ON LOCAL WISDOM - Purnadewi, Gusti Ayu Agung; Widana, I Wayan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2023)
This research aims to analyze the implementation of a PBL model based on local wisdom can improve science numeracy skills as well as evaluating and reflecting on the implementation of a PBL model based on local wisdom can improve learning activities. This research is classroom action research with research subjects in the VA class students of SDN 1 Dajan Peken Semester 1 of the 2023/2024 academic year and the research objects is science numeracy abilities and students' learning activities. This research was carried out in 2 cycles where each cycle consisted of planning, implementation, observation and reflection stages. Science numeracy ability data was collected using written tests referring to the Minimum Competency Assessment question model, while student learning activities were collected using observation sheets. This classroom action research to be successful and the cycle can be stopped, if it meets the following criteria: (a) the average value of science numeracy, absorption capacity, and percentage of completion respectively is at least 70.00; 70.00% and 85%; (b) minimally active student learning activities. If one or both of the success criteria above are not met, then the action research continues to the next cycle. Research data was analyzed descriptively qualitatively. The research results showed that: (1) in the initial reflection activity, the average science numeracy score was 62.94; absorption capacity 62.94%, and completion percentage 61.76%; (2) in cycle I, the average science numeracy score was 71.76; absorption capacity 71.76% and completion percentage 74.47%; and (3) in cycle II, the average science numeracy score was 77.06; absorption capacity 77.06% and completion percentage 88.24%. Classroom action research has met the success criteria in 2 cycles. Conclusion, the implementation of PBL model based on local wisdom can improve students' science numeracy skills and learning activities.